2022
DOI: 10.3389/fphar.2022.1008222
|View full text |Cite
|
Sign up to set email alerts
|

Salvia miltiorrhiza in cancer: Potential role in regulating MicroRNAs and epigenetic enzymes

Abstract: MicroRNAs are small non-coding RNAs that play important roles in gene regulation by influencing the translation and longevity of various target mRNAs and the expression of various target genes as well as by modifying histones and DNA methylation of promoter sites. Consequently, when dysregulated, microRNAs are involved in the development and progression of a variety of diseases, including cancer, by affecting cell growth, proliferation, differentiation, migration, and apoptosis. Preparations from the dried roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 239 publications
0
3
0
Order By: Relevance
“…In accordance with the preview studies, we found that baicalin significantly promoted both early and late apoptosis rates of Bcap-37 cells in a concentration-dependent manner. Apoptosis is a complex signaling pathway that is mediated by a series of apoptosis-related genes, including Bax, p38, p53, Bcl-2, and ERK1 (Lu et al, 2022; Wang et al, 2019). Also, a study revealed that baicalin promotes apoptosis of MCF-7 cells through up-regulating p53 and Bax (Wang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with the preview studies, we found that baicalin significantly promoted both early and late apoptosis rates of Bcap-37 cells in a concentration-dependent manner. Apoptosis is a complex signaling pathway that is mediated by a series of apoptosis-related genes, including Bax, p38, p53, Bcl-2, and ERK1 (Lu et al, 2022; Wang et al, 2019). Also, a study revealed that baicalin promotes apoptosis of MCF-7 cells through up-regulating p53 and Bax (Wang et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Salvia miltiorrhiza is extensively used as an herbal remedy in traditional Chinese medicine. The plant belongs to the Lamiaceae family, and its medicinal components include the roots or rhizomes [18]. The chemical compounds extracted from Salvia miltiorrhiza can be classified into two main groups: (i) fat-soluble tanshinone compounds, predominantly Tanshinone I and Tanshinone IIA, and (ii) water-soluble phenolic compounds, primarily including salvianolate [19].…”
Section: Discussionmentioning
confidence: 99%
“…Diue to the growing clinical demand for tanshinones, there has been a surge in research aimed at enhancing the effectiveness of tanshinones and maximizing their pharmacological impacts through the exploration of structure-activity relationships [20]. Several studies have demonstrated that the chemical components of Salvia miltiorrhiza, particularly tanshinone IIA, exhibit potent antitumor characteristics such as inhibiting cell proliferation, arresting the cell cycle, triggering apoptosis, and promoting autophagic cell death in different tumor cell varieties [18]. Tanshinone IIA serves as a representative compound in S. miltiorrhiza.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, literature has shown that S. miltiorrhiza plays a role in regulating the inflammatory microenvironment of the uterus [49], improving endometrial receptivity during the implantable window period [50], reversing drug resistance, inhibiting angiogenesis and lymphangiogenesis [51], and antioxidant activity [52], which remains to be further explored and verified. There is a lot of research on S. miltiorrhiza anti-EC, but the effect and mechanism of preventing cancer are still insufficient.…”
Section: Summary and Prospectmentioning
confidence: 99%